Autonomia feminina no processo de parto e nascimento: estudo fenomenológico na perspectiva das mulheres - Honnef, Fernanda (2019)
Childbirth as a physiological event of the sexual and reproductive life of women, must be accompanied and assisted so that it is experienced actively, exercising the role of protagonist of the process. In this way, the guiding question is: What are the motivations for the autonomous actions of women in the birth and birth process? As an objective, it seeks to apprehend the motivations of the autonomous actions of women in the process of birth and birth. It is a qualitative research, based on the social phenomenology of Alfred Schütz as a theoretical-methodological reference. In the southern region of Brazil, it had as scenario a university hospital. The phenomenological interview was used as a technique for data production with 15 puerperal women who were hospitalized in joint accommodation, in the period from September to December 2017. Analysis of the data occurred according to the basics of the adopted referential and with productions related to the object of study . The results show that the "reasons why" of the actions of women during the process of birth and birth both those actions during pregnancy and during labor occur due to fear of what they heard or because in previous births there was Pain complications and unwanted interventions. For the link with the companion and because he has experience or experience with the process of birth and birth. The reasons for the autonomous actions of women are aimed at receiving physical emotional support from the companion from the pregnancy, they want a calm delivery with less pain, fast and without interventions. And they intend to do the right things for the welfare of the child and that after the birth they are painless and active to take care of the children. We conclude that the autonomous actions of women in the process of birth and birth are inscribed in a social reality and are influenced by their specific biographical situation, and that their actions begin before pregnancy, in order to exercise their autonomy. And that this depends on the relationship with the professionals, when they stimulate the protagonism of women through a face-to-face relationship, or when they reinforce the submission of women when they submit the guidelines and adapt their behavior to what is placed in the institutions.